Survival Analysis of Under-Five Children with Severe Acute Malnutrition in Woldia Hospital: Retrospective Cohort Study - Aragaw Asfaw (Universitas Djuanda, 2021)
Abstract Background: Globally, 52 million children of age under five years were affected by acute malnutrition from which 17 million were severely wasted. In Ethiopia every month over 25,000 children with severe acute malnutrition are admitted to hospitals, if not identified early and treated properly, these children could die. Therefore this study aimed to assess the determinants of time to death of under-five children with SAM admitted to inpatient therapeutic feeding center in Woldia General Hospital. Methods: A retrospective cohort study was conducted. The study population were children with severe acute malnutrition aged from 0 to 59 months who have been admitted to woldia general hospital from September 2017 to August 2019.The sample was 150 that fulfils the inclusion criteria were included. Non parametric survival analysis was used to estimate survival time to death and Cox PH model was carried out to determine independent predictors. Results: The accounted proportion of death of under-five children in the study period was 10%. And the estimated mean survival time of the patient was 4.48 weeks. Both estimates was almost on the recommended Sphere standard which should < 10% and <4 weeks respectively. In the estimated model HR for age groups (24-35 months) is 0.000 with 95% CI [0.000-4.591], wasting is 0.010 with 95% CI [0.000-0.065], referred from is 0.000 with 95% CI [0.000-0.061], cough 133.04 with 95% CI [3.596-4922.83], HIV is 1209.61 with 95% CI [1.137-1286998.42], Iv antibiotic treatment is 0.000 with 95% CI [0.000-0.037] and amoxicillin is 0.001 with 95% CI [0.000-0.736] were significant predictors for time to death of under-five children with SAM. Conclusions: From the fitted model, age of the children, admission criteria, children referred from,cough, HIV, IV antibiotic treatment and Amoxicillin are the covariates that have significant effect on time to death of under five children by SAM at 5% level of significance. Early identifying cases and giving special attention for children with co morbidities such as HIV and cough is vital for decrease child mortality Ethiopia. Keywords: Severe acute malnutrition, inpatient, semi parametric, non parametric, death